2017
DOI: 10.1101/163873
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Light and growth form interact to shape stomatal ratio among British angiosperms

Abstract: Summary• In most plants, stomata are located only on the abaxial leaf surface (hypostomy), but many plants have stomata on both surfaces (amphistomy). High light and herbaceous growth form have been hypothesized to favor amphistomy, but these hypotheses have not been rigourously tested together using phylogenetic comparative methods.• I leveraged a large dataset including stomatal ratio, Ellenberg light indicator value, growth form, and phylogenetic relationships for 372 species of British angiosperms. I used … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
63
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(65 citation statements)
references
References 64 publications
2
63
0
Order By: Relevance
“…In particular, Muir (2018) observed an increase in SD ada , and hence SR, in response to greater light availability in the herbaceous species, whereas SD aba remained constant. Thus, greater SD ada and SR were favored when CO 2 strongly limited photosynthesis (as in open habitats) and photosynthesis strongly limited fitness (as in herbaceous species; Muir, 2018). Additionally, Milla et al (2013) suggested that 'adaxialization' of maximum conductance, by achieving greater SD ada compared with SD aba , was an important step during domestication of many crop species that are historically under selection for higher A net and TE i .…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…In particular, Muir (2018) observed an increase in SD ada , and hence SR, in response to greater light availability in the herbaceous species, whereas SD aba remained constant. Thus, greater SD ada and SR were favored when CO 2 strongly limited photosynthesis (as in open habitats) and photosynthesis strongly limited fitness (as in herbaceous species; Muir, 2018). Additionally, Milla et al (2013) suggested that 'adaxialization' of maximum conductance, by achieving greater SD ada compared with SD aba , was an important step during domestication of many crop species that are historically under selection for higher A net and TE i .…”
Section: Discussionmentioning
confidence: 83%
“…C 4 -g m increases with SD ada , SR and S mes Greater SD ada and SR are expected to decrease the CO 2 diffusion path length and increase S mes , thus leading to greater g m and A net (Muir, 2018;Drake et al, 2019), although no known studies to date provided direct evidence in support of this expectation. We tested this expectation in 18 amphistomatous C 4 grasses that are adapted to open habitats (Osborne & Freckleton, 2009) and varied greatly in SD aba and SD ada (Table 4), as reported previously (Taylor et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reaction-diffusion method (Parkhurst, 1977;Tholen and Zhu, 2011;Berghuijs et al, 2016;Ho et al, 2016) Can link detailed leaf anatomical traits to g m Provides a mechanistic explanation for g m response to pCO 2 Can account biochemical and environmental variable influencing g m including CA, light availability in subcellular compartments and leaf temperature Can account the influence of mitochondrial and chloroplast localization and the re-assimilation of (photo)respired CO 2 on g m (Parkhurst, 1978;Muir, 2018;Drake et al, 2019). This is because having stomata on both sides of the leaf has been proposed to reduce the average CO 2 diffusion path length within the leaf and create additional parallel pathways for CO 2 diffusion by increasing intercellular air spaces and hence S mes (Parkhurst, 1978;Mott and O'Leary, 1984;Muir, 2018). Consequently, it has been proposed that amphistomaty, if associated with greater adaxial stomatal densities (SD) and stomatal ratios (SR; ratio of SD ada to SD aba ), could lead to greater g m and A ne (Mott and O'Leary, 1984;Muir, 2018;Drake et al, 2019).…”
Section: Methodsmentioning
confidence: 99%
“…This is because having stomata on both sides of the leaf has been proposed to reduce the average CO 2 diffusion path length within the leaf and create additional parallel pathways for CO 2 diffusion by increasing intercellular air spaces and hence S mes (Parkhurst, 1978;Mott and O'Leary, 1984;Muir, 2018). Consequently, it has been proposed that amphistomaty, if associated with greater adaxial stomatal densities (SD) and stomatal ratios (SR; ratio of SD ada to SD aba ), could lead to greater g m and A ne (Mott and O'Leary, 1984;Muir, 2018;Drake et al, 2019). Fortunately, recent developments in 3-D reaction-diffusion models and 3-D image analysis of the leaf tissue are poised to potentially make strong inroads into our understanding of how the complex structure of the leaf influences the source/sink relationships of both CO 2 and H 2 O movement within a leaf (Ho et al, 2012;Berghuijs et al, 2015Berghuijs et al, , 2016Ho et al, 2016;Xiao and Zhu, 2017;Earles et al, 2018Earles et al, , 2019.…”
Section: Methodsmentioning
confidence: 99%